2022
DOI: 10.1371/journal.pone.0274577
|View full text |Cite
|
Sign up to set email alerts
|

Athletic trainers’ viewpoints of patient-centered care: Preliminary findings

Abstract: The core competency of patient-centered care (PCC) states that for positive patient outcomes, the provider must respect the patient’s views and recognize their experiences. The Athletic Training Strategic Alliance Research Agenda Task Force identified a profession-wide belief that examining the extent to which athletic trainers (ATs) provide PCC in their clinical practice would benefit the profession. To first address this line of inquiry, we must study the subjectivity of how ATs view PCC. This study used Q m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…It is important to increase the implementation of ICF components because it facilitates whole-patient care and allows interventions to be refocused to address the unique needs of each patient. Athletic trainers strongly believe that they are patient centered and have a willingness to be more patient centered, yet do not implement things such as the ICF framework into clinical practice [ 12 ]. This is why it is important to provide resources or educational opportunities for athletic trainers to learn more about certain components of the ICF framework.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to increase the implementation of ICF components because it facilitates whole-patient care and allows interventions to be refocused to address the unique needs of each patient. Athletic trainers strongly believe that they are patient centered and have a willingness to be more patient centered, yet do not implement things such as the ICF framework into clinical practice [ 12 ]. This is why it is important to provide resources or educational opportunities for athletic trainers to learn more about certain components of the ICF framework.…”
Section: Discussionmentioning
confidence: 99%
“…The athletic training profession has been slow to integrate the ICF framework into clinical practice. In a recent study exploring key components and viewpoints of patient-centered care, a large majority of athletic trainers reported that they did not consider the ICF framework a necessary component of patient-centered care [ 12 ]. When following up with these participants, when they were asked why they did not consider the ICF part of patient-centered care, many individuals reported simply not knowing what the ICF framework was or how to use it [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The central focus of the disablement model is to capture the patient perspective of their injury, considering each factor beyond the physical impairment where particular health constructs such as personal and environmental factors can be further evaluated [27]. Previous literature demonstrates that physical disability is more commonly focused on and considered during patient encounters in comparison to the rest of the patient's life [18,28]. Similarly, participants in our study demonstrated higher conscious competence and no conscious incompetence with limitations and impairments that patients may be facing.…”
Section: Disablement Model Frameworkmentioning
confidence: 99%
“…Further, chart audits may also provide value during this stage to promote where ATs can integrate a more holistic approach to patient care through documentation. Previous literature suggests that if ATs lack overall exposure to such frameworks, they cannot be expected to apply them as a method to determine clinical practice decisions and promote evidence-based medicine [28]. This is important for athletic training educators to reflect on current curriculum standards of applying the disablement model during didactic experiences.…”
Section: Resolving the Knowledge Gapmentioning
confidence: 99%